APPLICATION OF WATER POVERTY INDEX: A CASE STUDY OF UYO METROPOLIS IN AKWA IBOM STATE, NIGERIA. (International Journal of Engineering Sciences & Management Research, 2015)
Water poverty index (WPI) was used to evaluate the rate of water demand in some selected areas of Uyo metropolis in Akwa Ibom state, Nigeria. The composite index and the time series index approaches were used to measure the level of water stress in the four urban periphery communities selected. These communities are namely Ibiaku, Ekpri Nsukara, Nsukara Offot, Use Offot. Questionnaire and physical observations were the sources of data used. 30 respondents were sampled from each of the communities and simple descriptive statistics were used in analyzing the collected data. The showed that, using both the composite and time series approaches, Ibiaku was the least water stressed community while Ekpri Nsukara and Use Offot were the most stressed communities. The results further revealed that simple time analysis cannot link complex multidimensional aspects of water management together. The application of composite index approach to test the generated dataset provided flexible and strong decision making strategies in such a way as to construct a holistic water management tool to address the problems of poverty, and its relation to water access and use. It is recommended that improved water harvesting from both surface and underground sources should be harnessed to provide sufficient water for the water-stressed communities in Uyo Local Government Area in order to improve health and enhance economic productivity of the inhabitants of the communities.